Transformational Leadership Style, Teacher Competence, Teacher Performance and Organizational Culture at Al Ibrah Primary School, Gresik Regency: A Descriptive Statistical Review - Donna Ari Novita; Djoko Soelistya (Dinasti Publisher, 2024)
This study aims to descriptively explore the relationships between transformational leadership style, teacher competencies, organizational culture and teacher performance at Al Ibrah Primary School in Gresik district as an educational context. The research design used was descriptive quantitative. Data were collected through a questionnaire using a Likert scale distributed to 85 teachers of Al Ibrah Primary School. Data were analyzed using descriptive statistical techniques to describe the relationship between the variables studied. The results showed that the majority of respondents were female (62.4%) with the majority aged 29-32 years (24.7%) and had a Bachelor's degree (S1) (63.5%). The principal's transformational leadership style was rated high (total mean 4.21), especially in the aspect of performance evaluation (mean 4.28). Teachers' competencies are also high (total mean 4.17), with good implementation of the professional code of ethics and active participation in school activities. The organizational culture shows high support for innovation and risk-taking (total mean 4.08). These findings contribute to the understanding of how leadership and organizational factors impact educational outcomes, providing a basis for future research and practical strategies in educational settings.